Positive hepatitis B surface antigen after vaccination in a newborn - Martins,Mariana (2018)
Hepatitis B vaccination is included in the Portuguese national health plan. Vaccine-induced hepatitis B surface antigen positivity is described in literature, leading to diagnostic errors if the serological test is prematurely performed after vaccination. We report the case of a false positive transient B surface antigenemia in a premature baby born from a hepatitis B vaccinated mother. Caution is required when seropositivity is found after administration of hepatitis B vaccine in order to avoid anxiety in parents and unnecessary exams.